The logistical management of tertiary urethral disease in the United Kingdom: Implications from an online audit of male reconstructive urethral surgery. (July 2020) - Payne, Stephen R; Fowler, Sarah; Mundy, Anthony R
Objective: To determine those patient groupings, based on volume and risk, whose optimal urethral reconstructive management might be provided by a reorganisation of UK reconstructive surgeons. Methods: Between 2010 and 2017, ~689 men/year were enrolled onto an online audit platform collecting data about urethral reconstruction in the UK; this accrual was compared against hospital episode statistics (HES). The available workforce, and where this was based, was collected. Individual and institutional incumbent patient volumes, pathology, surgical complexity and outcomes from treatment were collated to stratify volume/risk groups. Results: More than 90% of all HES-recorded data were accrued, being provided by 50 surgeons at 39 operative sites. Most reconstructive surgery was provided at 10 centres performing >20 procedures/year. More than 50% of all interventions were of a high-volume low-risk type. Of activity, 32.3% was intermediate volume or moderate risk, and 12.5% of men presented for lower-volume or higher-risk procedures. Conclusion: Correlation of detailed volume/outcome data allows the definition of patient populations presenting for urethral reconstruction. Stratification of each group's management, to optimise the surgical outcome, may be applied to a hierarchical service delivery model based on the complexity of the patient's presenting urethral pathology. Level of evidence: Level IV